Penerapan Strategi Think Pair Share untuk Meningkatkan Hasil Belajar Siswa Kelas 5 MIN Singkawang Tahun 2023 - Evawani, Yuli (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
This research aims to describe the implementation of the Think Pair Share strategy to improve the learning outcomes of class V students at Madrasah Ibtidaiyah Negeri Singkawang in 2023. This research uses the Action Research method. The location of research was carried out at Madrasah Ibtidaiyah Negeri Singkawag for fifth-grade students. The collection technique uses data analysis techniques using qualitative data. The results of this research found that teacher activities at the 2nd meeting obtained an average score of 75.0%, which means an increase of 25.1% from the achievement at the 1st meeting where the average score was 48.9%. The results of student learning at the 1st and 2nd meetings can be seen from the results of the meetings, there has been a significant change, there has been an increase in those who read books before the lesson starts, although not all students have done so, there has been an increase in those who read (repeat) at home, those who like to pay attention to pictures- there is an increase in pictures in books, those who like to observe experiments and observe the steps their friends are doing there is an improvement, they often discuss with friends when studying there is an improvement, they are active in expressing opinions with friends there is an improvement, they interact with teachers, they do their homework there is an improvement even though they haven't yet everything, but there has been improvement so that the research has been successful at meeting 2.